Isolation and Molecular Characterization of Pasteurella multocida from Ducks - Sannegowda, Saritha N; Raju, Sumathi B; Govindaiah, Kavitha; Gomes, Amitha R; Yadav, Chaithra; Laxmanappa, Yashvanth S; Reddy , Sumanth Kumar R (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Duck pasteurellosis also called as Duck cholera is a highly contagious disease of ducks caused by Pasteurella multocida. It has been found to be most commonly occurring bacterial disease among semi-mature and mature birds with 5 to 100 % morbidity and 0.5 to 80 % mortality rates. The present study was conducted to investigate the suspected outbreak of pasteurellosis in a duck farm. The samples were collected from morbid and dead birds after conducting post-mortem examinations and processed for further isolation, identification and molecular characterization. The samples were found to be positive for Pasteurella multocida by cultural and biochemical tests and confirmed as Pasteurella multocida by using Pasteurella multocida species specific KMT1 primers and capsular type A specific primers. It was further processed for virulence-associated ompH gene. The purified Pasteurella multocida species specific KMT1 product was sequenced and based on nucleotides homology and phylogenetic analysis, the sample was having 99.76 % homology to Pasteurella multocida strain VP161 chromosome. Based on nucleotides homology and phylogenetic analysis of the capsular type-specific hyaD hyaC gene partial nucleotide sequences, the sample was having 98.60% homology to Pasteurella multocida strain PMISC1 HyaD (hyaD) gene specific for capsular type A.